Increased baclofen-stimulated G protein coupling and deactivation in rat brain cortex during development - Stöhr, Jiri; Bourova, Lenka; Hejnova, Lucie; Ihnatovych, Ivanna; Novotny, Jiri; Svoboda, Petr (Brain research. Developmental brain research, 2004)
The number and affinity of GABA(B) receptors (assayed by the specific antagonist [(3)H]CGP54626A) was unchanged when compared in carefully washed cerebrocortical membranes from young (12-day-old) and adult (90-day-old) rats. In contrast, high-affinity GTPase activity, both basal and baclofen-stimulated was significantly higher (by 45% and 56%, respectively) in adult than in young rats. Similar results were obtained by concomitant determination of agonist (baclofen)-stimulated GTP gamma S binding. Under standard conditions, baclofen-stimulated GTPase activity was further considerably enhanced by exogenously added regulator of G protein function, RGS1, but not by RGS16. RGS16 was able to affect agonist-stimulated GTPase activity only in the presence of markedly increase substrate (GTP) concentrations. RGS1 alone slightly increased GTPase activity in adult rats, but neither RGS1 nor RGS16 influenced GTPase activity in membrane preparations isolated from young animals. These findings indicate increasing functional activity of trimeric G protein(s) involved in GABAergic transmission in the developing rat brain cortex and suggest a high potential of RGS1 in regulation of high-affinity GTPase activity.
Keywords: proteiny; proteiny RGS; lékové interakce; Protein Binding; tritium; Proteins; organofosforové sloučeniny; Dose-Response Relationship, Drug; Baclofen; analýza rozptylu; novorozená zvířata; stárnutí; Analysis of Variance; krysa rodu Rattus; proteiny vázající GTP; radioligandová zkouška; zvířata; GABA agonisté; Aging; mozková kůra; Cerebral Cortex; RGS Proteins; Drug Interactions; Animals, Newborn; Guanosine 5'-O-(3-Thiotriphosphate); GTP-fosfohydrolasy; Male; Tritium; Radioligand Assay; vazba proteinů; Organophosphorus Compounds; Rats; GABA Agonists; vztah mezi dávkou a účinkem léčiva; guanosin 5'-O-(3-thiotrifosfát); baklofen; Animals; mužské pohlaví; GTP-Binding Proteins; GTP Phosphohydrolases